The multistep hypothesis of ALS revisited - Hardiman, Orla; Mc Laughlin, Russell (Wolters Kluwer Health, 2018)
Objective: Amyotrophic lateral sclerosis (ALS) incidence rates are consistent with the hypothesis that ALS is a multistep process. We tested the hypothesis that carrying a large effect mutation might account for≥1 steps through the effect of the mutation, thus leaving fewer remaining steps before ALS begins. Methods: We generated incidence data from an ALS population register in Italy (2007–2015) for which genetic analysis for C9 or f72, SOD1, TARDBP, and FUS genes was performed in 82% of incident cases. As confirmation, we used data from ALS cases diagnosed in the Republic of Ireland (2006–2014). We regressed the log of age-specific incidence against the log of age with least-squares regression for the subpopulation carrying disease-associated variation in each separate gene. Results: Of the 1,077 genetically tested cases, 74 (6.9%) carried C9 or f72 mutations, 20 (1.9%) hadSOD1mutations, 15 (1.4%) had TARDBP mutations, and 3 (0.3%) carried FUS mutations. In the whole population, there was a linear relationship between log incidence and log age (r2= 0.98) with a slope estimate of 4.65 (4.37–4.95), consistent with a 6-step process. The analysis for C9 or f72-mutated patients confirmed a linear relationship (r2= 0.94) with a slope estimate of 2.22 (1.74–2.29), suggesting a 3-step process. This estimate was confirmed by data from the Irish ALS register. The slope estimate was consistent with a 2-step process for SOD1and with a 4-step process for TARDBP. Conclusion: The identification of a reduced number of steps in patients with ALS with genetic mutations compared to those without mutations supports the idea of ALS as a multistep process and is an important advance for dissecting the pathogenic process in ALS.
Keywords: Amyotrophic lateral sclerosis (ALS); Confidence interval (CI); Piemonte and Valle d’Aosta Register for ALS (PARALS)